PENGEMBANGAN BOOKLET SUB MATERI PERAN TUMBUHAN DI BIDANG EKONOMI UNTUK PEMBUATAN STICK PEPAYA - Hastuti, Rini; Daningsih, Entin; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of booklet using submaterial plant role in economy, as well as to know the students responses to this booklet. The booklet also contain how to make papaya stick and to practicum activities on the submaterial plant role in economy. The method was Research and Development (R & D) consisting of six out and stages from ten stages, namely potential and problems, data collection, product design, design validation, design revision and limited trials. Validation was carried out by five validators consisting of two lecturers and three Biology teachers from senior high school. The validation was carried out divided into two steps. The first step was validation of booklet instrument and the second step was booklet validation. The students responses to the booklet was used a questionnaire and categories according to Likert. Based on validation CVI of booklet was 0,95 and categoris valid according Lawse method. And edition, the students responses to the booklet was also very hight 87,76%. Therefore the booklet was submaterial plant role of economy was feasible tobe use in learning proccess. Keywords: Booklet, Feasibility, R&D Method, Response, Stick Papaya